USES OF PUBLISHED FINANCIAL STATEMENTS IN FUNDING DECISIONS - Eltahir Khalifa, Hussein Mohammed; ELbashir Abdelrahman, Siddig Mohammed (International Journal of Research -GRANTHAALAYAH, 2020)
The study aimed to show financial items that used in the analysis of the decision to grant funding or not, to let parties in the funding decision of the important indicators even be no need to borrow, study the problem of the lack of use of published financial statement analysis we used a sample of a private company, Hypotheses (financial reports iteming and analysis methods lead to make funding decision, there are ways, methods and tools of procedural accounting represents a tools of helping the parties to pay loans. Result: Priority financial statements are important grant funding decision, there is a relationship between tripping to fulfill their financial obligations and fairness of the financial reports submitted. Recommendations: Must increase disclosures in the financial statements published, new studies to read of financial statements polices and for grant funding policies before the financial reports published analysis.